Designing BaTiO3/carbon nanotube core-shell hybrids to achieve polyvinylidene fluoride composites with high dielectric properties. (24th April 2019) - Fan, Benhui; Zhou, Mingyu; Zhang, Chong; Liu, Yu; He, Delong; Bai, Jinbo
Abstract: The synthesized core–shell hybrids, BaTiO3 (shell) @ carbon nanotubes (core), (BT@CNT), can make the polyvinylidene fluoride (PVDF) matrix composite to exhibit high dielectric permittivity ( ε ′) but low dielectric loss (tan δ ) when approaching the percolation threshold. High ε ′ is attributed to BT coating which can strengthen the interfacial polarization in the composite. Low tan δ is attributed to the formation of the structure: CNT → BT → PVDF with the gradually decreasing dielectric properties from the centers of hybrid to the surrounding borders of PVDF. Additionally, AC conductivity of the composites can be deduced by the self-consistent effective medium (SCEM) approximation, which helps to understand the conductive behavior of CNT with a ceramic buffer layer in PVDF matrix more comprehensively.